2023
DOI: 10.1186/s12905-023-02629-0
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual disturbances and its association with sleep disturbances: a systematic review

Bomin Jeon,
Jihyun Baek

Abstract: Background Menstrual disturbances harm women’s health, and general well-being. As growing evidence highlights the relationship between sleep and menstrual disturbances, it is imperative to comprehensively examine the association between sleep and menstrual disturbance considering the multiple dimensions of sleep. This systematic review aims to identify the association between sleep and menstrual disturbances by evaluating using Buysse’s sleep health framework. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 71 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…In addition, 59% of the female participants were deemed as bad sleepers while men exhibited 33% of bad sleepers. It is worth considering that hormonal factors, such as the menstrual cycle, may contribute to gender differences in sleep quality ( 23 , 24 ) and sleep disorders could affect the menstrual cycle ( 25 ). However, the menstrual cycle of the females was not controlled in this study and consequently, this is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 59% of the female participants were deemed as bad sleepers while men exhibited 33% of bad sleepers. It is worth considering that hormonal factors, such as the menstrual cycle, may contribute to gender differences in sleep quality ( 23 , 24 ) and sleep disorders could affect the menstrual cycle ( 25 ). However, the menstrual cycle of the females was not controlled in this study and consequently, this is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Wunsch et al 22 ) indicated that physical activity and exercise may be able to buffer the negative effects of stress on health-related outcomes. Also, a recent systematic review concluded that poor sleep satisfaction and efficiency, sleepiness during waking hours, and shorter sleep duration were associated with menstrual disturbances including premenstrual syndrome, dysmenorrhea, abnormal menstrual cycle, and heavy bleeding during periods 23 ) . For these reasons, future research can benefit from consideration of these relating points.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, due to feelings of embarrassment, on rare occasions, women may choose to request sick leave and disclose their PMS symptoms, primarily because of concerns about the appropriateness of taking time off work [ 159 ]. A large case-control study showed a higher prevalence of productivity-related impairments in the PMS group than in the group without PMS [ 160 ]. PMS also affects sleep quality.…”
Section: Potential Impact Of Pms and Pmdd On Quality Of Life Interper...mentioning
confidence: 99%